2014
DOI: 10.7326/m13-2946
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Socioeconomic Disadvantage and 30-Day Rehospitalization

Abstract: Background Measures of socioeconomic disadvantage may enable improved targeting of programs to prevent rehospitalizations, but obtaining such information directly from patients can be difficult. Measures of US neighborhood socioeconomic disadvantage are more readily available, although rarely employed clinically. Objective To evaluate the association between neighborhood socioeconomic disadvantage at the census block-group level, as measured by Singh’s validated Area Deprivation Index (ADI), and 30-day rehos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
872
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,011 publications
(968 citation statements)
references
References 41 publications
36
872
4
Order By: Relevance
“…ADI scores were calculated using the 2013 American Community Survey 5-year averages. Higher ADI values (and therefore percentiles) represent greater degrees of socioeconomic contextual disadvantage [14]. We found that the distribution of ADI values was similar for our study region as for the entirety of North Carolina (Supplement 1).…”
Section: Area Deprivation Indexmentioning
confidence: 55%
“…ADI scores were calculated using the 2013 American Community Survey 5-year averages. Higher ADI values (and therefore percentiles) represent greater degrees of socioeconomic contextual disadvantage [14]. We found that the distribution of ADI values was similar for our study region as for the entirety of North Carolina (Supplement 1).…”
Section: Area Deprivation Indexmentioning
confidence: 55%
“…In the current study, we used the ADI, a composite score derived from US census data, as an area‐level indicator of social deprivation. Among US adults, the ADI has been associated with all‐cause mortality and 30‐day rehospitalization 18, 45. Results from the current analysis suggest that the ADI may not be independently associated with ASCVD risk and should not be used for ASCVD risk prediction among US adults.…”
Section: Discussionmentioning
confidence: 73%
“…For sensitivity analyses, we used 2 other measures of SES: (1) neighborhood poverty, as defined by the percentage of individuals living below the poverty line in residential ZCTAs (dichotomized as ≤20% and >20%), and (2) area deprivation index (ADI). The ADI uses 17 US Census poverty, education, housing, and employment indicators to characterize neighborhood socioeconomic disadvantage and has been correlated with a number of health outcomes including mortality and rehospitalizations 18, 19. We used the methodology described by Kind et al by estimating ADI at a 5‐digit ZCTA level (Table S1) and then divided ADI into 4 “national ADI” categories: ADI‐0 (least deprived) composed 85% of the population, whereas ADI‐1, ‐2, and ‐3 were equally sized 5% groupings, with deprived neighborhoods in ascending order (ADI‐3 indicated most deprived).…”
Section: Methodsmentioning
confidence: 99%